دور السياحة التضامنية في دعم التنمية الريفية: تقييم واقع السياحة الريفية بولاية سوق أهراس وفقا لتحليل SWOT - كريم، عمامرة; زيراوي، عادل (جامعة عباس لغرور خنشلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2022)
هدفت الدراسة الحالية إلى إبراز أهمية السياحة الريفية (التضامنية) في تحقيق التنمية الريفية في الجزائر، من خلال تقييم واقع السياحة في الريف وفقا لتحليل SWOT، ولقد طبقنا هذا التحليل في ولاية سوق أهراس. وتوصلت الدراسة إلى جملة من النتائج أهمها: تعد السياحة التضامنية حلا استراتيجيا لتنمية الريف الجزائري، بحيث أنها تكرس علاقة رابح رابح بين السواح وسكان الريف، تعمل على التثمين الاقتصادي للتراث المادي واللامادي، تحقق التنمية الريفية المستدامة، تخلق الثروة وتوفر مناصب شغل للسكان، وتعتبر بديلا غير مكلفا للسائح. The present study aims to highlight the importance of rural tourism "solidarity tourism" to achieve rural development in Algeria, by evaluating the reality of rural tourism according to the "S.W.O.T" analysis, and we have applied this analysis in the city of Souk Ahras. This study reached an important number of results such as: - Solidarity tourism is a strategic solution for the development of the Algerian countryside as it devotes the (win-win) relationship between tourists and rural population. - It works on the economic evaluation of the tangible and intangible heritage, as it achieves sustainable rural development and crates wealth. - Solidarity tourism provides jobs for residents and is an inexpensive alternative for tourists.
Keywords: التنمية الريفية -- السياحة الريفية -- التنمية المستدامة -- الجزائر